Themes on development economics - Roy, Joyashree (Ed.); Gupta, Manash Ranjan (Ed.) (Ahmedabad Allied, 2000)
This volume compiles a selection of papers that were presented at the Fifth and Sixth Annual Conference on comtemporary issues in development economics. These papers have a wide range of coverage and problems of trade,agriculture,industryenergy, planning
Keywords: Economic development; Economics; Economic policy